Plasma Amyloid-β Oligomerization Tendency Predicts Amyloid PET Positivity - Pyun JM (Dove Medical Press, 2021)
Jung-Min Pyun,1 Ji Sun Ryu,2 Ryan Lee,2 Kyu Hawn Shim,3 Young Chul Youn,4 Nayoung Ryoo,5 Sang-Won Han,5 Young Ho Park,5 Sungmin Kang,2 Seong Soo A An,6 SangYun Kim5 1Department of Neurology, Uijeongbu Eulji Medical Center, Eulji University, Uijeongbu-si, Gyeonggi-do, Republic of Korea; 2Research and Development, PeopleBio Inc., Seongnam-si, Gyeonggi-do, Republic of Korea; 3Department of Neurology, Veterans Medical Research Institute, Veterans Health Service Medical Center, Seoul, Republic of Korea; 4Department of Neurology, Chung-Ang University College of Medicine, Seoul, Republic of Korea; 5Department of Neurology, Seoul National University College of Medicine and Seoul National University Bundang Hospital, Seongnam-si, Gyeonggi-do, Republic of Korea; 6Department of Bionanotechnology, Gachon University, Seongnam-si, Gyeonggi-do, Republic of KoreaCorrespondence: SangYun KimDepartment of Neurology, Seoul National University Bundang Hospital, 82, Gumi-ro 173 Beon-gil, Bundang-gu, Seongnam-si, Gyeonggi-do, 13620, Republic of KoreaTel +82 31 787 7462 Fax +82 31 787 4059Email neuroksy@snu.ac.krPurpose: Among other emerging amyloid-targeting blood-based biomarkers, Multimer Detection System-Oligomeric Amyloid-β (MDS-OAβ) measures dynamic changes in concentration of oligomeric amyloid-β (OAβ), which is considered the main pathogenic culprit of Alzheimer’s disease (AD), in plasma after spiking with synthetic amyloid-β (Aβ). We aimed to investigate the predictability of MDS-OAβ on amyloid positron emission tomography (PET) positivity.Patients and Methods: A total of 96 subjects who visited Seoul National University Bundang Hospital for medical check-up complaining of cognitive decline and had undergone extensive medical assessment were recruited. Amyloid statuses were dichotomized into positive or negative based on visual assessment of amyloid PET. Plasma OAβ concentration was measured by MDS-OAβ. In the previous validation study, 0.78ng/mL was established as the cut-off value and the plasma OAβ concentration higher than or equal to the cut-off value was defined as MDS-OAβ positive.Results: MDS-OAβ positivity could discriminate amyloid PET positivity with the AUC value of 0.855 (95% CI 0.776– 0.933). Adding MDS-OAβ positivity to prediction models including age, MMSE score, and APOE ϵ4 status improved performance up to the AUC value of 0.926 (95% CI 0.871– 0.980).Conclusion: The Aβ oligomerization tendency in plasma could predict amyloid PET positivity with high performance, and, when it is combined with age, MMSE score, and APOE ϵ4 status, predictability was improved substantially. This suggests the potential of MDS-OAβ as a useful initial stage test in the clinical and research fields of AD.Keywords: multimer detection system-oligomeric amyloid-β, Aβ oligomer, predictability, amyloidopathy, blood-based biomarker